Echoes of Neglect: Navigating Sibling Rivalry as the Unheard Child - Julliene S Del Mundo; Natasha Joy A Macalanda (Advanced Qualitative Research, 2025)
This interpretative phenomenological analysis (IPA) study delves into the personal experiences of children who feel unheard within the context of sibling rivalry. It focuses on how these children perceive their roles in the family, particularly in situations where they feel overshadowed or ignored in comparison to their siblings. The study involved semi-structured interviews with seven (7) children aged 18-37 years old, who shared their feelings and stories about sibling rivalry, especially when they felt excluded from family attention or support. The analysis revealed three (3) key themes: (1) Favoritism, which refers to the practice of giving unfair preferential treatment to one person or group at the expense of another. (2) Detachment, described as an emotional withdrawal to avoid pain or rejection, often develops in childhood. (3) Self-Doubt, referred to as the feeling of questioning one’s own worth and decisions, often caused by being ignored or dismissed by important people like parents. The study underscores the importance of fostering a more open, inclusive family environment where every child's voice is valued and heard, especially for those who may feel lost in the shadows of sibling dynamics. These findings highlight the emotional toll of sibling rivalry and suggest ways for families to better address the needs of all children, ensuring they feel seen and supported.